MYXOID LIPOSARCOMA ORIGINATING IN THE ANTERIOR MEDIASTINUM - Khan, Mohammad Harisullah; Kashif, Ramsha; Khan, Hamza Abdur Rahim; Fatimi, Saulat Hasnain (Journal of Ayub Medical College Abbottabad, 2016)
Myxoid liposarcomas of the head and neck are mostly metastatic in nature, with the primary lesion usually in lower extremities or retroperitoneum. Primary mediastinal liposarcomas are even rarer. Although there have been previous cases reporting their incidence, there is no evidence of any case comprising of both the neck and the mediastinal region yet. We here present a case of a 43 year old male with a primary liposarcoma of the myxoid subtype originating in the anterior mediastinum. This is the first time such a case has presented in literature. The patient presented with a right sided neck swelling associated with pain and shortness of breath upon lying down. CT neck revealed an enhancing mass extending from right cervical region to axilla and encasing the subclavian artery and involving a portion of the right lung. The patient underwent wide local excision of the mass along with chemoradiotherapy to prevent recurrence. Keywords: Myxoid; liposarcoma; soft tissue sarcomas; head and neck